2010
DOI: 10.5254/1.3512954
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sine Versus Pulse Waveform Effects on Fatigue Crack Growth Behavior of Nr, Sbr, and Br Compounds

Abstract: Fatigue crack growth experiments on carbon black-filled rubber compounds have been carried out to evaluate the influence of testing conditions over different compound formulations. Investigations on the influence of waveform, data acquisition, and compound formulation have been performed on strip-tensile specimens reproducing the model of crack opening. The response of three different compound formulations (based on either natural rubber, butadiene rubber, or styrene-butadiene rubber) to the application of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Crack initiation is the initial phase of fatigue failure for any kind of materials and hence it is very crucial to understand this phenomenon in detail including contributing factors and underlying mechanisms. In the recent past, several literatures emphasized about the damage mechanics on the basis of material behavior, environmental condition, thermal and mechanical parameter 1–7 . These studies revealed that type of fillers and their structure plays a significant role to govern the failure mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Crack initiation is the initial phase of fatigue failure for any kind of materials and hence it is very crucial to understand this phenomenon in detail including contributing factors and underlying mechanisms. In the recent past, several literatures emphasized about the damage mechanics on the basis of material behavior, environmental condition, thermal and mechanical parameter 1–7 . These studies revealed that type of fillers and their structure plays a significant role to govern the failure mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of different waveforms on crack propagation was investigated by Harbour et al, 4 who determined the effect of dwell time using different sine wave cycles, a comparison between pure-shear and a single-edge notched tension (SENT) specimen using a real pulse waveform was not investigated. In a previous contribution, 9 the authors showed that fatigue crack growth determination with strip-tensile tests has some limitations; a typical case was a polybutadiene rubber (BR) compound in which the crack propagated faster than the maximum allowed frame rate of the video acquisition system, so that data could not be acquired at all. The purpose of this investigation is to clarify the influence of different sample geometries on rubber crack propagation as well as the effect of different waveforms on compound formulations that differ only in polymer type.…”
Section: Introductionmentioning
confidence: 99%